Odors from Sewage Sludge and Livestock: Associations with Self-Reported Health. (November 2014) - Wing, Steve; Lowman, Amy; Keil, Alex; Marshall, Stephen W.
Objectives: Class B treated sewage sludge (TSS) contains microbes and toxicants and is applied to land in areas where livestock wastes may be present. We evaluated relationships of reports of TSS and livestock odors with acute symptoms and excessive flies. Methods: A total of 158 adults living near liquid TSS application sites, 85 living near cake TSS application sites, and 188 living in comparison areas responded to a household survey regarding odors, health, and demographics. We identified symptom groups using factor analysis. We used generalized estimating equations to fit linear models for associations between factor scores and odors, and Poisson models for associations with specific symptoms. Results: Most factor scores were similar between exposure groups. Covariate-adjusted z-scores for lower respiratory symptoms were 0.28 (95% confidence interval [CI] −0.10, 0.65) higher among residents who reported moderate to very strong liquid TSS odor than among residents in comparison areas, and 0.28 (95% CI 0.05, 0.50) higher among residents who reported moderate to very strong livestock odor compared with residents reporting no or faint livestock odor. The factor score for dermatologic conditions was higher among residents who reported higher liquid sludge odor (0.27, 95% CI −0.13, 0.68), primarily due to skin rash (prevalence ratio = 2.21, 95% CI 1.13, 4.32). Excessive flies were reported twice as commonly among respondents who reported moderate to very strong TSS odor than among other residents. Conclusions: Reported odors from TSS and livestock were associated with some acute symptoms. Health departments should monitor land applications of human and animal wastes and conduct surveillance of health problems reported by neighbors.